CdTe1‐xSex/Cd0.5Zn0.5S core/shell quantum dots: core composition and property. (15th August 2013) - Yang, Ping; Cao, Yongqiang; Li, Xiaoyu; Zhang, Ruili; Liu, Ning; Zhang, Yulan
ABSTRACT Alloy CdTe1‐xSex quantum dots (QDs) have been fabricated by an organic route using Cd, Te and Se precursors in a mixture of trioctylamine and octadecylphosphonic acid at 280 °C. The variation of photoluminescence (PL) peak wavelength of the CdTe1‐xSex QDs compared with CdTe QDs confirmed the formation of an alloy structure. The Se component drastically affected the stability of CdTe1‐xSex QDs. A Cd0.5Zn0.5S shell coating on CdTe1‐xSex cores was carried out using oleic acid as a capping agent. CdTe1‐xSex/Cd0.5Zn0.5S core/shell QDs revealed dark red PL while a yellow PL peak was observed for the CdTe1‐xSex cores. The PL efficiency of the core/shell QDs was drastically increased (less than 1% for the cores and up to 65% for the core/shell QDs). The stability of QDs in various buffer solutions was investigated. Core/shell QDs can be used for biological applications because of their high stability, tunable PL and high PL efficiency. Copyright © 2013 John Wiley & Sons, Ltd.